Beauty and the beast. The beast's tale - Reaves, Mallory (Tokyopop, 2017)
" ... a bright, beautiful and independent young woman, is taken prisoner by a beast in a catle. Despite her fears, she befriends the castle's enchanted staff and learns to look beyond the Beast's hideous exterior and realize the kind heart and soul of the true Prince inside. This manga explores the Beast's struggle as he tries to move on from his past and learn what it is to love..."--Back cover.